Moisture Sources and Rainfall δ¹⁸O Variability over the Central Andes of Peru—A Case Study from the Mantaro River Basin - Apaéstegui Campos, James Emiliano (2023)
The Mantaro River Basin is one of the most important regions in the central Peruvian Andes in terms of hydropower generation and agricultural production. Contributions to better understanding of the climate and hydrological dynamics are vital for this region and constitute key information to support regional water security and socioeconomic resilience. This study presents eight years of monthly isotopic precipitation information (δ¹⁸O, Dxs) collected in the Mantaro River Basin. The isotopic signals were evaluated in terms of moisture sources, including local and regional climatic parameters, to interpret their variability at monthly and interannual timescales. It is proposed that the degree of rainout upstream and the transport history of air masses, also related to regional atmospheric features, are the main factors influencing the δ¹⁸O variability. Moreover, significant correlations with precipitation amount and relative humidity imply that local processes in this region of the Andes also exert important control over isotopic variability. Two extreme regional climate events (the 2010 drought and the 2017 coastal El Niño) were evaluated to determine how regional atmospheric circulation affects the rainfall isotope variability. Based on these results, recommendations for hydroclimate studies and paleoclimate reconstructions are proposed in the context of the Mantaro River Basin. This study intends to encourage new applications considering geochemical evidence for hydrological studies over the central Andean region.